Hyperoside Protected Against Oxidative Stress-Induced Liver Injury via the PHLPP2-AKT-GSK-3β Signaling Pathway In Vivo and In Vitro - Haiyan Xing; Ruoqiu Fu; Caiyi Cheng; Yongqing Cai; Xianfeng Wang; Dongmei Deng; Xiaoyuan Gong; Jianhong Chen (Frontiers Media S.A., 2020)
Hyperoside, isolated from Drosera rotundifolia L., seeds of Cuscuta chinensis Lam., or Hypericum perforatum L., originally showed to possess an antifungal and antibacterial activity, while recently showed the protective effects against oxidative stress-induced liver injury. This study investigated such a protective effect of hyperoside and the underlying molecular mechanisms in vitro and in carbon tetrachloride (CCl4)-injured rat livers. The data showed that hyperoside was able to prevent the oxidative stress-induced liver morphological changes and CCl4-induced rat liver injury. Hyperoside reversed the decrease of superoxidase dismutase (SOD) level and the increase of malondialdehyde (MDA) level in vivo. Moreover, hyperoside regulated the pleckstrin homology (PH) domain leucine-rich repeat protein phosphatase 2 (PHLPP2)-protein kinase B (AKT)-glycogen synthase kinase 3β (GSK-3β) signaling pathway in tert-butylhydroquinone (t-BHP)-treated liver cells, e.g., Hyperoside reduced PHLPP2 expression to activate AKT phosphorylation, induce GSK-3β phosphorylation, and then increased nuclear factor erythroid-2-related factor 2 (Nrf2) nuclear translocation, reduced nuclear translocation of phosphorylated Fyn, and promoted heme oxygenase-1 (HO-1) expression in vivo and in vitro. In contrast, siRNA-mediated knockdown of PHLPP2 expression enhanced hyperoside-mediated activation of the AKT-GSK-3β kinase pathway in liver cells. In conclusion, the present study demonstrated that hyperoside could protect against oxidative stress-induced liver injury by regulating the PHLPP2-AKT-GSK-3β signaling pathway in vivo and in vitro.